Implementation of Restorative Justice in Resolving Minor Crimes: An Empirical Study at the Grobogan Police Resort: Implementasi Restorative Justice Dalam Penyelesaian Tindak Pidana Ringan: Studi Empiris di Kepolisian Resor Grobogan - Dwi Muryanto; Lailasari Ekaningsih; Ridho Sa'dillah (Journal of Creative Power and Ambition (JCPA), 2026)
The accumulation of minor criminal offense (tipiring) cases represents a persistent structural problem within Indonesia's criminal justice system. This study examines the mechanisms by which restorative justice (RJ) is applied to tipiring cases at Grobogan District Police (Polres Grobogan), the challenges encountered by investigators, and a comparative evaluation of RJ's effectiveness against formal prosecution. An empirical juridical approach with a qualitatively dominant mixed-method design was employed. Data were gathered from 45 purposively selected case files (out of 180 cases handled in 2022-2024), eight key informant interviews, field observations, and focus group discussions. Findings reveal that 71.1% of tipiring cases were resolved via RJ in an average of 14.3 days, compared to 127.8 days through formal channels. Victim satisfaction averaged 4.2 out of 5 under the RJ track versus 3.1 for formal procedures, and one-year recidivism rates were markedly lower (8.3% vs. 22.7%). Core challenges include the absence of standardized internal SOPs, insufficient formal RJ training among active investigators, residual retributive orientations among some victims, and inadequate post-agreement monitoring. The study concludes that RJ implementation at Polres Grobogan is comparatively effective, though it requires systematic strengthening through internal regulatory development, investigator capacity-building, and more robust oversight mechanisms.